已知列表 x = [1, 2],那么执行语句 x.append([3]) 之后,x的值为:
A: [[3],1,2]
B: [1,3,2]
C: [1,2,3]
D: [1,2,[3]]
A: [[3],1,2]
B: [1,3,2]
C: [1,2,3]
D: [1,2,[3]]
举一反三
- 已知列表 x = [1, 2],那么执行语句 x.append([3]) 之后,x的值为: A: [[3],1,2] B: [1,3,2] C: [1,2,3] D: [1,2,[3]]
- 已知列表 x = [1, 2,3],那么执行语句 x.append([3]) 之后,x的值为_____________。 A: [1, 2,3,[3]] B: [1, 2,3,3] C: [1, 2,[3]] D: 1,2,3,[3]
- 已知列表x = [1, 2],那么执行语句x.extend([3]) 之后, x的值为___()_______。 A: [[1], [2]] B: [1, 2, 3] C: [3, 1, 2] D: [1, 2, [3]]
- 已知列表 x = [1, 2, 3],那么执行语句 x.insert(0, 4)之后,x的值为___________。 A: [1, 2, 4,3] B: [1, 2, 3] C: [4, 1, 2, 3] D: [1,2, 3, 4]
- 已知列表x=[1,2],那么执行语句x.append(3)之后,x的值为() A: [1,2] B: [1,2,3] C: [1,2,[3]] D: []